Aflatoxin Contamination in Peanuts Commercially Available in Sri Lanka - Dissanayake, D.M.M.P.; Manage, P.M. (My University, 2009)
Peanut is one of the oil seeds available in Sri Lanka. Peanuts and peanut products are considered as popular food items among all age groups of population, especially in urban areas. People prefer to buy peanut based food items as snacks. Peanut is shown to be a good substrate for the growth of Aspergiillus sp. and for the production of aflatoxins. Aflatoxins are potent teratogenic, mutagenic, and carcinogenic mycotoxin proven to be contained in food and feed. Present work was carried out as a preliminary study to determine the level of aflatoxin contamination in commercially available roasted and fried peanut samples collected from venders in Colombo city, Sri Lanka. Samples were tested for aflatoxins by the CB method of the Association of Official Analytical Chemists. Degree of aflatoxin contamination was determined by densitometric evaluation. For the method validation of aflatoxin analysis, two extraction and cleanup procedures were performed. Chloroform/water extraction and Sep Pac cartridge clean up procedure were selected as the most reliable methods. Results of the study showed that 6.6 % of the tested peanut samples were moderately contaminated (12.5 ppb) and the remaining was fallen into the category of uncontaminated according to the FAO and WHO standards. Overall result of the study showed that the samples were not significantly contaminated and unnecessary doubt on aflatoxin contamination is not needed. However, effective constant monitoring, surveillance and control programs on aflatoxins contamination are important to protect consumers from aflatoxin toxicities. Therefore, screening programs which prevents unsuitable products entering to the market are recommended to evaluate the contamination.
Keywords: Peanut; Aflatoxin; Method validation; Aspergillus jlavus; A.parasiticus